An integrated system at the Bleien Observatory for mapping the Galaxy. Issue 2 (28th September 2016) - Chang, Chihway; Monstein, Christian; Akeret, Joel; Seehars, Sebastian; Refregier, Alexandre; Amara, Adam; Glauser, Adrian; Stuber, Bruno
Abstract: We describe the design and performance of the hardware system at the Bleien Observatory. The system is designed to deliver a map of the Galaxy at 990–1260 MHz for studying the foreground contamination of low-redshift ( z = 0.13–0.43) H i intensity mapping experiments as well as other astronomical Galactic studies. This hardware system is composed of a 7 m parabolic dish, a dual-polarization corrugated horn feed, a pseudo-correlation receiver, a Fast Fourier Transform spectrometer and an integrated control system that controls and monitors the progress of the data collection. The main innovative designs in the hardware are (1) the pseudo-correlation receiver and the cold reference source within (2) the high dynamic range, high frequency resolution spectrometer and (3) the phase-switch implementation of the system. This is the first time these technologies are used together for an L -band radio telescope to achieve an electronically stable system, which is an essential first step for wide-field cosmological measurements. This work demonstrates the prospects and challenges for future H i intensity mapping experiments.